Organizational Behavior Dynamics and Governance Effectiveness in the Transformation of Educational Management - Devi Fatwanti; Abidin Nasyar; Mukhriji Mukhriji; Zakaria Syafei; Eka Sari Mulyani; Rijal Firdaos (EDUJAVARE: International Journal of Educational Research, 2026)
This article discusses the concept of organization and organizational behavior in the context of educational organization management. Organization is understood as a structured social unit, consisting of individuals who work together consciously to achieve common goals. In the world of education, organizations play an important role in organizing effective, efficient, and directed learning processes. Meanwhile, organizational behavior is a study of how individuals, groups, and organizational structures interact with each other and influence the effectiveness and productivity of the organization. This article highlights the elements of the organization, the goals and benefits of the organization, and the dynamics of organizational behavior such as motivation, leadership, and organizational culture. In addition, opportunities and challenges such as workforce diversity, innovation, and the importance of ethics in organizational behavior are also discussed. A deep understanding of this concept is expected to help improve the quality of educational institution management and create a conducive and productive work environment